The Influence of Premiums, Claims, Investment Results and Underwriting on Profits in Sharia Insurance Companies - Banurea, Lusi Yashinta; Hafizh, Muhammad (Neraca Keuangan : Jurnal Ilmiah Akuntansi dan Keuangan, 2024)
This research aims to determine the effect of premiums, claims, investment returns and underwriting on profits in sharia life insurance companies. In this research, a panel data regression analysis approach is used. The sampling method in this research uses a purposive sampling method. This research uses quantitative methods in the form of secondary data contained in the annual financial reports of each company. This research uses the Eviews 10 tool. The sample for this research is 8 sharia life insurance companies registered with the financial services authority (OJK) for the 2018-2022 period. The results of this study show that partially premiums, claims, investment returns and underwriting have no effect on profits at Sharia life insurance companies and simultaneously premiums, claims, investment returns and underwriting have an effect on profits at Sharia life insurance companies.